Consumer Rights Awareness and its Effect on Consumerism in Meerut - Rashmi; Yudhvir Singh (International Journal of Engineering and Management Research, 2024)
Consumerism has been defined as a social movement seeking to augment the rights and powers of consumers in relation to sellers (Kotler, 2000). It has spread to developing countries including India but majority of Indian consumers have been observed to be relatively passive in utilizing their rights and the established consumer protection mechanisms. Consumer exploitation has therefore continued unabated in the market place. The present study is aimed at investigating the level of consumer rights awareness and the effect of consumer rights awareness on consumerism in the Meerut region through a survey of household consumers in the area. It covers the aspect of general awareness among consumers in the area under study regarding consumer protection and specific awareness of provision of consumer protection act 1986. A pre-designed self-administered questionnaire was used for data collection. The research observed that a lot of consumers are being exploited even with the awareness about their rights under legal framework of consumer protection act 1986. Despite so many legal provisions made by Government of India for the well being of consumers, but the complete protection is still awaited. The study recommends for a policy on consumer education and activation in the region. It also recommends that manufacturers should establish a division for consumer affairs to listen to consumer complaints addresses their issues.